1984
DOI: 10.1038/clpt.1984.210
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose ceftriaxone kinetics in liver insufficiency

Abstract: The disposition profile of ceftriaxone was studied in eight normal subjects and in 15 subjects with various degrees of chronic liver damage (alcoholic fatty liver [FL] and cirrhosis without [C] and with [CA] ascites) who received bolus injections of ceftriaxone, 1 gm iv. Plasma protein binding fell in all. As a result, mean free fraction in plasma rose between 140% (FL) and 320% (CA). An exceptionally large rise (1270%) occurred in one subject with CA when the condition was aggravated by renal impairment. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
6
21
1
Order By: Relevance
“…The maximum binding capacity (N3) was found to be 1 mol of drug per mol of albumin, and the association constant (K3) was 2.5 x 104 M-'. These values are in close agreement with those reported previously (3,4,17,18,22,27).…”
Section: Methodssupporting
confidence: 83%
“…The maximum binding capacity (N3) was found to be 1 mol of drug per mol of albumin, and the association constant (K3) was 2.5 x 104 M-'. These values are in close agreement with those reported previously (3,4,17,18,22,27).…”
Section: Methodssupporting
confidence: 83%
“…However, the free fraction of antibiotic did increase because of the reduced protein binding. These results differ slightly from those observed in the studies with patient volunteers cited above (Jehl et al, 1990;Mazzei et al, 1993;Stoeckel et al, 1984). Unlike the single-dose ceftriaxone pharmacokinetic studies in uninfected cirrhotic patients, we measured peak serum concentrations at steady state on day 3 of therapy in rats with pneumococcal pneumonia.…”
Section: Discussioncontrasting
confidence: 52%
“…In a single-dose pharmacokinetic study, Stoeckel et al, (1984) found that when compared with normal controls, patients with chronic liver disease had significantly decreased mean nonrenal clearance of unbound ceftriaxone. The elimination half-life (t 1/2 b), however, was not influenced by chronic liver insufficiency (Stoeckel et al, 1984). Others (Hary et al, 1989) conducted a similar study in cirrhotic patients with ascites and also found no change in t 1/2 b.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, its ease of use and the quality of its tolerability, which have been shown in other patient categories, encourage us to use it on a regular basis when an infection caused by susceptible organisms occurs during the final 3 months of * Corresponding author. pregnancy (25,27,29). It has been shown that the systemic and local tolerabilities of CTX are excellent, with the absence of any nephrotoxicity (15,16).…”
mentioning
confidence: 99%
“…pregnancy (25,27,29). It has been shown that the systemic and local tolerabilities of CTX are excellent, with the absence of any nephrotoxicity (15, 16).…”
mentioning
confidence: 99%